Fourth-generation wireless networks [ applications and innovations - Adibi, Sasan , 1970-; Mobasher, Amin , 1978-; Tofigh, Tom , 1955- (Gale virtual reference library, 2010)
"This book presents a comprehensive collection of recent findings in access technologies useful in the architecture of wireless networks"-- Provided by publisher